Bioversity International - Research for our future - Bioversity International (2012)
Bioversity International is a research-for-development organization seeking solutions to global issues through the use and conservation of agricultural and forest biodiversity.Bioversity International’s purpose is to investigate the use and conservation of agricultural and forest biodiversity in order to achieve better nutrition, improve livelihoods, enhance agricultural and forest sustainability and enable productive and resilient ecosystems.